Horatio Sharpe papers - Sharpe, Horatio, 1718-1790.
Correspondence, financial accounts, and other papers relating to the Stamp Act, tariff, American loyalist sentiment, and politics at the time of the Revolution. Correspondents include Sharpe's brothers, Joshua Sharpe, Philip Sharpe, and William Sharpe, and Frederick Calvert (Lord Baltimore), William Dyall, and Samuel Ridout.
In part, handwritten transcripts.
British colonial governor of Maryland.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Baltimore, Frederick Calvert, -- Baron, -- 1731-1771 -- Correspondence; Dyall, William -- Correspondence; Ridout, Samuel -- Correspondence; Sharpe, Joshua -- Correspondence; Sharpe, Philip -- Correspondence; Sharpe, William, -- active 1756 -- Correspondence; Great Britain; American loyalists; Tariff; Maryland -- Politics and government -- To 1775.; Maryland -- Politics and government -- 1775-1783.; United States -- Politics and government -- To 1775.; United States -- Politics and government -- 1775-1783.; Governors -- Maryland